IGF-2-mediated hypoglycemia: a case series and review of the medical therapies for refractory hypoglycemia - Albert Vu; Constance Chik; Sarah Kwong (Endocrinology, Diabetes & Metabolism Case Reports, 2024)
Non-islet cell tumour hypoglycemia (NICTH), typically mediated by insulin-like growth factor 2 (IGF-2), is a rare but highly morbid paraneoplastic syndrome associated with tumours of mesenchymal or epithelial origin. Outside of dextrose administration and dietary modification which provide transient relief of hypoglycemia, resection of the underlying tumour is the only known cure for NICTH. Available medical therapies to manage hypoglycemia include glucocorticoids, recombinant growth hormone, and pasireotide. We report two cases of IGF-2 mediated hypoglycemia. The first was managed surgically to good effect, highlighting the importance of a timely diagnosis to maximise the likelihood of a surgical cure. The second patient had unresectable disease and was managed medically, adding to a growing number of cases supporting the efficacy of glucocorticoids and recombinant growth hormone in NICTH.